The Effectiveness of Emotion-Focused Therapy (EFT) in Improving Attachment Styles and Marital Satisfaction of Married Women - Ekhtiyari Amiri, Raziyeh (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The present study aimed to determine the effectiveness of emotion-focused therapy (EFT) in improving attachment styles and marital satisfaction of married women. Method: The present research was a semi-experimental study with a pretest-posttest design and a control group with a three-month follow-up. The statistical population consisted of women who visited counseling centers in Mazandaran province from May to July 2021. Forty-two women, who volunteered to participate in the research, answered the Collins and Read adult attachment Scale (RASS) (1990) and Enrich Marital Satisfaction Scale (EMS) (1987). After screening, 30 women were selected and randomly assigned to the experimental group of emotion-focused therapy (n=15) and the control group (n=15). The experimental group was subjected to Johnson's emotion-oriented intervention (2012) for eight 90-minute sessions, and the data were analyzed using repeated-measures mixed model analysis of variance. Results: The results indicated the effect of the emotion-focused intervention on secure attachment style (F=3.21, P= 0.042) with an effect size of 0.10, anxious attachment style (F=2.13, P=0.048) with an effect size of 0.06, avoidant attachment style (F=7.76, P=0.038) with an effect size of 0.14, and marital satisfaction (F=5.73, P=0.024), and this effect was stable at the follow-up stage. Conclusion: This intervention caused women in the experimental group to focus on their husbands' behavior and to stop the use of the above-mentioned communication barriers, and also increased their tolerance, and could improve their relationships and increase their resilience by learning the right communication program. Therefore, they were considered effective interventions to improve the insecure and anxious attachment style and marital satisfaction